2017
DOI: 10.4103/2277-9175.190994
|View full text |Cite
|
Sign up to set email alerts
|

Central Beneficial Effects of Trimetazidine on Psychomotor Performance in Normal Healthy Volunteers

Abstract: Background:Trimetazidine is a fatty oxidation inhibitor, leading to shifting of energy substrate from fatty acid oxidation toward glucose oxidation that leads to the reduction of oxygen requirement. The aims of the present study were to elucidate the effects of trimetazidine on psychomotor performance and vigilance on normal healthy volunteers.Materials and Methods:A total of 234 subjects (age 22–25 years) were recruited in this study. The volunteers were randomizing into two groups with 117 volunteers in each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Thus, a placebo may cause upgrading or deterioration of human cognitive function depending on specific expectations. Therefore, the effect of placebo may be revealed on human cognitive functions and reaction time during psychomotor performance, vigilance, and working memory testing depending on stereotype stimulations ( Al-Kuraishy, Al-Gareeb, & Ashor, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a placebo may cause upgrading or deterioration of human cognitive function depending on specific expectations. Therefore, the effect of placebo may be revealed on human cognitive functions and reaction time during psychomotor performance, vigilance, and working memory testing depending on stereotype stimulations ( Al-Kuraishy, Al-Gareeb, & Ashor, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The range of fusion-flicker frequency was from zero to 60 Hz. Good values for CFFA should be more than 30 Hz and less than 30Hz for CFFD (CFFF= CFFA+CFFD/2) ( Al-kuraishy & Al-Gareeb, 2017 ; Angeli, Veres, Nagy & Schneider 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Mice with orexin knockout are subjected to narcolepsy and excessive daytime sleepiness. [ 7 ] Alizamini et al . 's study showed that central administration of orexin leads to stimulation of locomotion, psychomotor performance, body temperature, and energy expenditure.…”
Section: Introductionmentioning
confidence: 99%
“…In the RCT conducted by Al-Kuraishy et al, the authors showed that trimetazidine enhances psychomotor parameters in non-athletic volunteers. This work was published in 2017, three years after the WADA trimetazidine ban (51). Vitale et al demonstrated that trimetazidine improves exercise performance in patients with pe-ripheral arterial disease, but they did not examine healthy volunteers or athletes (52).…”
Section: Trimetazidinementioning
confidence: 99%